THE DEVELOPMENT OF KATAYA (REPLIKA PETA BUDAYA) MEDIA IN THEMATIC LEARNING ON THE 4TH GRADE - Fauziyah, Sarah; Nulhakim, Lukman; Yuliana, Rina (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2019)
Abstract. This research aims to know the steps of development and the feasibility of Kataya (Replika Peta Budaya) media in 4th grade of elementary school. The research method used is the Research and Development (R & D) method with reference of Borg and Gall development model which developed by Sugiyono. This model consisting of 10 stages; (1) the potential and the problems (2) collecting the information (3) product design (4) design validation (5) design revision (6) small group product trial (7) product revision (8) large group product trial (9) final product revision (10) mass production. This research is limited only in 6 stages. Expert validation was carried out by media experts, material experts and education experts, with the research subjects of 4th grade students of SDIT Dauroh, amounting to 24 students, from the data obtained get the average expert validation score of 92.67%, with the